2017
DOI: 10.1080/14767058.2017.1364721
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal abnormal width of the cavum septum pellucidum – MRI features and neurodevelopmental outcome

Abstract: To the best of our knowledge, this is the first study to examine the outcome in narrow and wide CSPs detected prenatally. An abnormal width of the CSP prenatally, without an associated fetal abnormality such as aneuploidy, appears to have normal outcome. MRI should be offered when an absence of the CSP is suspected on US to rule out narrow CSP, which seems to be a benign finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The likely explanation being the capacity for plasticity in the early CNS, which allows for a range of normal or mildly abnormal outcomes despite malformations or insults. Evidence for this has emerged from studies that contain neurodevelopmental outcomes after several years of follow up, and which demonstrate a high proportion of neurologically normal outcomes despite structural malformations 2225. Thus a longer period of follow up in the present study may allow for brain maturation and emergence of the likely long-term neurodevelopmental status for these subjects against which in utero GM assessment could be assessed.…”
Section: Discussionmentioning
confidence: 79%
“…The likely explanation being the capacity for plasticity in the early CNS, which allows for a range of normal or mildly abnormal outcomes despite malformations or insults. Evidence for this has emerged from studies that contain neurodevelopmental outcomes after several years of follow up, and which demonstrate a high proportion of neurologically normal outcomes despite structural malformations 2225. Thus a longer period of follow up in the present study may allow for brain maturation and emergence of the likely long-term neurodevelopmental status for these subjects against which in utero GM assessment could be assessed.…”
Section: Discussionmentioning
confidence: 79%
“…The cavum septum pellucidum (CSP) is a fluid‐filled cavity found between the leaves of the septum pellucidum in the fetus . Enlarged CSP has often been considered a marker for fetal neural maldevelopment affecting the septo‐hippocampal and limbic systems, and a maker for aneuploidy .…”
Section: Discussionmentioning
confidence: 99%
“…8 The cavum septum pellucidum (CSP) is a fluidfilled cavity found between the leaves of the septum pellucidum in the fetus. 12 Enlarged CSP has often been considered a marker for fetal neural maldevelopment affecting the septo-hippocampal and limbic systems, 13 and a maker for aneuploidy. 7 Several investigations have shown that a wide (>1 cm) CSP and persistence of a CSP beyond infancy served as significant markers of cerebral dysfunction and may be accompanied by a significantly increased risk of mental retardation, developmental delay and neuropsychiatric disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Mild ventriculomegaly (ventricle width of 10–12 mm) without other systemic malformations is usually considered to have normal neurodevelopmental processes [ 16 ]. Without of aneuploidy and other associated fetal abnormalities, the neurodevelopment appears to be normal in the abnormal width of the CSP prenatally [ 17 ]. Because of the prognosis, these fetuses were considered to be low risk and selected in the study.…”
Section: Methodsmentioning
confidence: 99%